Redesigning the Madrasah Teacher Professional Education Curriculum through Ecotheological Literacy Integration to Address the Global Environmental Crisis - Rhamadanus Saefulloh (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
The current environmental crisis is fundamentally a moral and spiritual challenge, yet the response from Islamic educational institutions, particularly madrasahs, remains constrained by a significant gap in ecotheological literacy among educators. This policy naskah addresses the critical lack of environmental spirituality integration within the Teacher Professional Education program and other in-service training structures, which are presently dominated by the rigid administrative and technical-pedagogical standards of the New Public Management paradigm. Such a bureaucratic focus has marginalized the transformative religious values essential for planetary survival, leading to a systemic